Anestezjologia i intensywna terapiaExperience of NovoSeven administration in the management of severe haemorrhage following cardiac surgery - Michalska-Krzanowska, Grażyna; Stanek, Mirosława; Grzegrzółka, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: Severe bleeding in cardiac surgery is often difficult to manage. The efficacy of traditional drugs is variable, which is why it is necessary to use newer agents for beneficial control and prevention of massive bleeding. Aim: of this study is clinical evaluation of efficacy of rFVIIa in the treatment of bleeding during and after cardiac surgery. Material and Methods: rFVIIa was used in 20 adult patients who underwent open heart surgery. All patients had normal coagulation parameters before surgery. We compared the amount of blood lost within 12 hours before and 12 hours after giving rFVIIa, and the dynamics of bleeding before and after treatment. The dosage of rFVIIa was 39.23±20.70 µ/kg. Results: Indications for administration of rFVIIa were considered when there was postsurgical bleeding in the absence of surgical sources of bleeding and lack of efficacy of conventional haemostatic procedures. After administration of the first median dose (14.45-81.35 µg/kg) rFVIIa bleeding stopped in 11 patients and markedly decreased in 7 patients. 2 patients who did not benefit from initial rFVIIa administration received an additional dose with good results. After rFVIIa dosing transfusion for PRBC was reduced. Conclusions: rFVIIa produces a potent haemostatic effect in bleeding events complicating cardiosurgical interventions.